El microcrédito y la inclusión financiera en mujeres del distrito de Contamana año 2022 - Melendez Hidalgo, Lidiani (2022)
The objective of this report was to determine the relationship between microcredit and financial inclusion in women in the District of Contamana, year 2022, it was inclined towards a descriptive - correlational level investigation and was developed under a non-experimental design, whose study population was made up of 286 women who acquired credit in said district; For the collection of information, the survey was used as a technique and the questionnaire as an instrument. After verifying the results, it was determined that the microcredit has been behaving adequately (30%) because the financial entities always provide them with credit alternatives to start a business; Likewise, it always requires some type of guarantee to grant a loan; likewise, the level of financial inclusion is very high (27%) since they always have a savings account and they always know the interest rates offered by the finance company. Finally, it has been determined that there is a considerable significant relationship between microcredit and financial inclusion in women in the District of Contamana 2022, corroborated by a coefficient of 0.727 and a significance of 0.000.